Effect of basalt fibre hybridisation on post-impact mechanical behaviour of hemp fibre reinforced composites. (August 2015) - Dhakal, Hom Nath; Sarasini, Fabrizio; Santulli, Carlo; Tirillò, Jacopo; Zhang, Zhongyi; Arumugam, Vellayaraj
Abstract: A major limitation to the spreading of natural fibre reinforced composites in semi-structural components is their unsatisfactory impact performance. As a potential solution, the production of synthetic/plant fibre hybrid laminates has been explored, trying to obtain materials with sufficient impact properties, while retaining a reduced cost and a substantial environmental gain. This study explores the effects of hybridisation of basalt fibre on post-impact behaviour and damage tolerance capability of hemp fibre reinforced composites. All reinforced laminates were impacted in a range of energies (3, 6, and 9 J) and subjected to both quasi-static and cyclic flexural tests with a step loading procedure. The tests have also been monitored by acoustic emission (AE), which has confirmed the existence of severe limitations to the use of natural fibre reinforced composites even when impacted at energies not so close to penetration and the enhanced damage tolerance offered by the hybridisation with basalt fibers.